The Other Brother: Re-experiencing spontaneous moments from domestic life. - Helmes, John; Hummels, Caroline; Sellen, Abigail (TEI 2009 - Proceedings of the 3rd International Conference on Tangible and Embedded Interaction, 2009)
In this paper, we describe “The Other Brother”, a semiautonomous device that captures images and video of spontaneous moments in the course of everyday life. It was our goal to design a situated, tangible object for life-time capturing purposes. In addition to describing the object and our deployment findings, this paper also discusses the design process and the goals we were aiming to achieve through the design. This was an iterative process from initial sketches, concepts and physical explorations towards a final design and several prototypes. The final prototype acts as an agent that behaves to some extent autonomously, capturing spontaneous moments that enable people to reexperience these moments in a playful way. Testing The Other Brother in a domestic environment, we describe several findings of the impact of the object in the home, reflect on several design and interaction issues, and discuss future directions for continuation of this research.